Understanding the Relationship between CSR and Dividend Policy: Review and Future Prospects - Chettri, Navin; C. Kabra, Kailash; Rani, Neelam (Indonesian Journal of Sustainability Accounting and Management, 2022)
The study explores and highlights the relationship between dividend payout (DP) policy and corporate social responsibility (CSR). For this purpose, the author used a survey method to find previous research articles that have discussed this relationship. The study’s findings suggest that CSR and DP, individually and with other variables, have been considerably researched. However, when it comes to the relationship between the two variables, the research is only about a decade old. Thus, minimal research has explored this relationship and has concentrated only on developed economies. Most of these researchers have found a positive relationship between the two variables, despite taking different proxies to measure CSR, which is contrary to the Resource-Based Theory. The author concluded that there is a lack of research focusing on the relationship between the two major corporate decisions. Thus, no theory(ies) explains the relationship, and corporate managers, policymakers, investors, and even researchers have not paid enough attention to the association and its implications.